Particle Size and Internal Structure of Deformed Coal: Microstructure and Adsorption/Desorption Characteristics of CO2 and CH4 - Li, Xiaoshi; Ju, Yiwen; Song, Yu; Yan, Zhifeng; Li, Qiangguang (Frontiers in Earth Science, 2022)
Structural deformation has a very important effect on the particle size and adsorption/desorption properties of coal, which is widely distributed in China, but there are few studies in this area. The effects of particle size and internal structure on the pores and adsorption properties of deformed coal were studied, and the influence of structural deformation was analyzed. Eight undeformed and deformed coal samples were progressively crushed from 0.12 to 0.15 mm (100–120 mesh), 0.18 to 0.25 mm (60–80 mesh), and 0.42 to 0.84 mm (20–40 mesh), and subsequently, adsorption/desorption characteristics of CO2 and CH4 and pore structure analyses were performed on all the grain size fractions. The coal size fraction has a slightly smaller influence on CO2 adsorption than on CH4 adsorption. Deformation can promote gas desorption, which increases as the deformation increases. Moreover, deformation can reduce the effect of granularity and internal structure on gas adsorption capacities. The 60–80 mesh is suggested to be the optimal size for deformed coal to achieve the ideal adsorption/desorption effect without eliminating the influence of structural deformation. However, below 100–120 mesh is recommended to reduce the impact of structural deformation on data processing and analysis when the sample contains both deformed and undeformed coals.